2021
DOI: 10.48550/arxiv.2111.09391
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishing accretion flares from massive black holes as a major source of high-energy neutrinos

Abstract: High-energy neutrinos have thus far been observed in coincidence with timevariable emission from three different accreting black holes: a gamma-ray flare from a blazar (TXS 0506+056), an optical transient following a stellar tidal disruption (AT2019dsg), and an optical outburst from an active galactic nucleus (AT2019fdr). Here we present a unified explanation for the latter two of these sources: accretion flares that reach the Eddington limit. A signature of these events is a luminous infrared reverberation si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 39 publications
(57 reference statements)
2
36
0
Order By: Relevance
“…This represents the first direct evidence of multi-messenger TDE emission, and accompanying modelling confirmed that conditions in these sources were consistent with requirements for the detection of a high-energy neutrinos [256][257][258][259]. An archival search has since identified AT2019aalc as a third candidate neutrino-TDE, with a combined statistical significance of 3.7σ [260]. A complimentary probe of TDE emission, searching for archival cross-correlation with neutrinos at ∼10 TeV energies, constrained the overall contribution of the TDE population to no more than 39% of the astrophysical neutrino flux under the assumption of an unbroken E −2.5 power law [261].…”
Section: Robert Steinsupporting
confidence: 70%
“…This represents the first direct evidence of multi-messenger TDE emission, and accompanying modelling confirmed that conditions in these sources were consistent with requirements for the detection of a high-energy neutrinos [256][257][258][259]. An archival search has since identified AT2019aalc as a third candidate neutrino-TDE, with a combined statistical significance of 3.7σ [260]. A complimentary probe of TDE emission, searching for archival cross-correlation with neutrinos at ∼10 TeV energies, constrained the overall contribution of the TDE population to no more than 39% of the astrophysical neutrino flux under the assumption of an unbroken E −2.5 power law [261].…”
Section: Robert Steinsupporting
confidence: 70%
“…After the submission of this work, we notice recent reports on more neutrino events associated with the time-variable emission from accreting SMBHs (van Velzen et al 2021a;Reusch et al 2021), among which AT2019fdr is a TDE candidate in a Narrow-Line Seyfert 1 AGN in which the BLR clouds should exist. Moreover, the neutrino events lag the optical outbursts by half one year to one year (van Velzen et al 2021a), consistent with the assumption that clouds exist at the distance of ∼ 10 −2 pc from the central BH if the outflow velocity is in the order of 10 9 cm s −1 .…”
Section: Conclusion and Discussionmentioning
confidence: 86%
“…There are signs that some clouds are located closely to the central SMBH in this source. AT2019dsg showed strong dust echo, which appears almost simultaneous with the burst in g-and r-band of ZTF (van Velzen et al 2021a). Considering that the dust echo flux is linearly proportional to the dust covering factor, the covering factor Cv should be around 10%.…”
Section: Introductionmentioning
confidence: 96%
“…in GeV and TeV energies). Nevertheless, neutrinos are proposed be from the accretion flares in the super-Eddington systems, from which the lack of detecting γ-ray emissions are due to the severe γγ absorption (van Velzen et al 2021). Actually, evidences that the incoming neutrino events are associated with flaring blazars are cumulating.…”
Section: Discussion and Summarymentioning
confidence: 99%